Residential Consumers Lifestyle Energy Usage and Energy Efficiency in Selected States in Malaysia - Daud S.; Wan Hanafi W.N.; Ayodele B.V.; Rajadurai J.; Mustapa S.I.; Ahmad N.N.; Wan Abdullah W.M.T.; Toolib S.N.; Ashaari M.J.; Afsarizal H.A. (MDPI, 2024)
In recent decades, significant changes have occurred in the consumer lifestyle and energy consumption structure. In order to foster a more holistic understanding of how residential consumers use energy in their everyday life and how it affects energy efficiency, individual data about energy-related behaviour in six primary areas, namely, housing, mobility, diet, consumption, leisure activities, and information, were studied. Specifically, the objective of this study is to investigate energy efficiency behaviour based on residential consumers lifestyles. An exploratory pilot study with a total of 50 respondents was carried out in month of July. Data were collected from residential consumers from six states in Peninsular Malaysia and were analysed using the Partial Least Square Structural Equation Modelling approach. The result showed that consumption, housing, and information are the dominant direct contributors to energy efficiency. By understanding these lifestyles, researchers and policymakers can better understand consumer energy consumption behaviour and design targeted interventions to encourage energy efficiency and conservation. The paper highlights the need for further research on consumer lifestyles and their contribution to energy efficiency. It also provides findings from this study that was used to refine the research tools for future research. 2023 by the authors.